Una propuesta de diseño curricular para una iniciativa de educación económica, financiera y de emprendimiento en el Colegio San Bartolomé La Merced (2020)
This document presents the curriculum design for an economic, financial and entrepreneurship education initiative at the San Bartolomé La Merced school in Bogota, Colombia. This is done using the Backward Design model, a curriculum design method proposed by the Understanding by Design (UbD) conceptual and referencing framework. For the curriculum design, as a source of information, I used the pedagogical guidelines for Economic and Financial Education and the general guidelines for the promotion of entrepreneurship culture in educational establishments, both proposed by the Ministerio Nacional de Educación (MEN); the Financial Competence Framework proposed by the International Student Assessment Programme (PISA) and finally the school's Institutional Educational Project. The results are summarized in a curriculum that promotes the construction of basic knowledge of economics, finance, and entrepreneurship at the level of middle education. This curriculum presents four objectives set out as understandings, competencies that will be developed to achieve these objectives and their respective evaluation criteria and, finally, a teaching methodology based on the Problem-Based Learning model. The results show how Economic and Financial Education can be implemented in the school curriculum in order to provide students with the necessary tools for informed and responsible decision making on economic and financial issues of their daily life.